Characteristics and Treatment of Wastewater from the Mercaptan Oxidation Process: A Comprehensive Review - Cubillos-Montecino, F; Gacitua-Bustos, J; Huilinir-Curio, C; Montalvo-Martinez, S (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sulfur compounds are removed from petroleum by the addition of sodium hydroxide at a very high concentration. As a result, a residue called spent soda or spent caustic is generated, being extremely aggressive to the environment. In this work, the chemical properties of this residue are described in detail. The sodium hydroxide remains that have not reacted, sulfur compounds, and organic matter are the primary pollutants reported. Additionally, the main characteristics of the methods of treatment used to reduce them are described. This review comes from comprehensive and updated research and bibliographic analysis about the investigation on the topic. The advantages and disadvantages of the different treatment methods are highlighted. We established some criteria to set out when assessing the application of each one of these treatments is considered.